Studying the Effect of Laser Rays on Blood Gases - Jalil Nahi, Ayat Hussein; Habib Dikh , Taiba Radhi; Ali Khudair, Istabraq Ibrahim; Hamza, Istabraq Hadi Kazem (American Journal of Botany and Bioengineering, 2024)
In this research, blood samples were taken for 5 people (4 males and female) at Al-Husseini Hospital in Karbala governorate under the supervision of the head of the intensive care laboratory department. At the level of blood gases, they were irradiated at the University of Karbala, College of Science, Department of Physics, with a multiplexed Nd: Yag laser with a wavelength of 532 nm and a capacity of 23 milliwatts in green color and at specific times for each blood sample 5 minutes and at a distance of 18 cm, then we measured the percentage of gases Again for the same blood samples, but after laser irradiation and we compared the results before and after laser irradiation. The results showed us that the percentage of PH and oxygen decreased after exposure to the laser, and the percentage of carbon dioxide increased in all cases, and the reason for changing the most appropriate is due to two types of interaction For the laser used for this study, these reactions are the photochemical reaction and the second reaction is the thermal reaction.